Acceptance of Cloud Computing Technology on Student Academic Performance - Riskinanto, Anggar; Kelana, Bayu (STMIK PONTIANAK, 2022)
Technology, especially the Internet, has become a part of everyday human life, where the solution is developing cloud computing. It provides virtual resources so that they can be accessed anytime and anywhere. The use of this service is growing not only for personal purposes, but also for academic purposes, such as for exchanging information and collaborating. Its use has become part of the teaching and learning process, but its effect on academic performance is not yet clearly known. For this reason, this study was conducted to determine academic performance which is influenced by the adoption of cloud computing technology among students. The research was conducted on students at STIMIK ESQ. The research is quantitative and uses online questionnaires to obtain data. The number of samples obtained was 151 consisting of various study programs. Based on the analysis conducted using SEM-PLS, it was found that almost all hypotheses were accepted. From this analysis, it is also found that the strongest influence is on the construct of Attitude to Continued Use Intentions. This shows that the desire for sustainable use of cloud computing is influenced by students' attitudes towards this technology.